Pathology and diagnosis of proliferative and ulcerative dermatitis associated with Tunga penetrans infestation in cattle. (January 2015) - Marin, Raul E.; Houston, Robin; Omanska-Klusek, Alicja; Alcaraz, Ana; Garcia, Jorge P.; Uzal, Francisco A.
Tunga penetrans is the smallest biting flea known. In cattle, infestation by T. penetrans (tungiasis) typically affects the skin of the distal legs, udder, prepuce, and perianal area. A detailed clinical and pathologic description of bovine tungiasis, together with electron microscopy and molecular diagnostics to establish the identity of the parasite are described. Ninety percent of the cows and heifers and 80% of the bulls in a herd in northwest Argentina had proliferative and ulcerative skin lesions affecting the coronary band, interdigital space, heels, and rudimentary toes of the fore and/or rear limbs, teats, and/or prepuce. These proliferative lesions had multiple large cavities filled with hemorrhagic fluid, necrotic debris, and Tunga spp. parasites. Histologically, the skin showed diffuse papillary epithelial hyperplasia with severe orthokeratotic hyperkeratosis, and it was multifocally ulcerated and inflamed. Multifocally, sections of arthropod parasites were observed embedded in the epidermis and dermis with the posterior end toward the surface. Images of wet mounts and scanning electron microscopy of the parasite showed morphologic characteristics compatible with Tunga spp. Polymerase chain reaction followed by sequencing of the cytochrome c oxidase subunit II and the internal transcribed spacer region indicated 99% homology to published T. penetrans sequences. Tungiasis should be considered as a differential diagnosis for proliferative lesions in skin of cattle.